Use of BNP and CRP as Biomarkers in Assessing Cardiovascular Disease:Diagnosis Versus Risk - Miller, Virginia M.; Redfield, Margaret M.; McConnell, Joseph P. (Current Vascular Pharmacology, 2007)
Biomarkers are used in medicine to facilitate diagnosis, assess risk, direct therapy and determine efficacy of treatment. Sensitivity and specificity are essential in order for a biomarker to be useful. Brain natriuretic peptide (BNP) and C-reactive protein (CRP) are considered biomarkers of cardiovascular disease. However, they differ in function, sensitivity and specificity. BNP is released from the myocardium in response to myocardial stretch, a clear cause and effect relationship; therefore, it is useful in the diagnosis of heart failure when patients present with dyspnea of unknown origin and to assess treatment in high risk patients with diagnosed heart failure. Sex and age based reference ranges and partition values are established from clinical trials and from populations screened for the absence of cardiovascular disease. Highly sensitive and reproducible methods are also available to measure CRP. However, although CRP is associated with adverse cardiovascular events, unlike BNP, multiple stimuli increase production of CRP. Therefore, elevation in CRP is not specific to cardiovascular disease. Partition values for CRP and cardiovascular risk based on epidemiological studies predict risk for populations but may not always be useful when used alone to predict individual risk or to direct therapy. Given the non-specific stimuli which affect circulating concentrations of CRP, using CRP to monitor treatment to reduce cardiovascular risk may provide little benefit without understanding or targeting the underlying causes for its elevation.
Keywords: hormone replacement therapy